The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.3748/wjg.v13.i48.6512
|View full text |Cite
|
Sign up to set email alerts
|

New anti-proliferative agent, MK615, from Japanese apricot “Prunus mume” induces striking autophagy in colon cancer cells in vitro

Abstract: MK615 has an anti-neoplastic effect against colon cancer cells. The effect may be exerted by induction of apoptosis and autophagy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 29 publications
2
29
0
2
Order By: Relevance
“…Previous studies have revealed that MK615 has anti-neoplastic effects against gastric cancer [1] , breast cancer [2] , hepatocellular carcinoma [3] , and colon cancer [4] . The mechanisms responsible for the anti-neoplastic effect of MK615 include induction of apoptosis [1,2] and autophagy [4] , and suppression of Aurora A kinase [3] in cancer cells. However, the entire mechanisms of the anti-neoplastic effects of MK615 have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed that MK615 has anti-neoplastic effects against gastric cancer [1] , breast cancer [2] , hepatocellular carcinoma [3] , and colon cancer [4] . The mechanisms responsible for the anti-neoplastic effect of MK615 include induction of apoptosis [1,2] and autophagy [4] , and suppression of Aurora A kinase [3] in cancer cells. However, the entire mechanisms of the anti-neoplastic effects of MK615 have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…the extract of ume has been reported to exert anticancer effects against gastric (3), breast (7), hepatocellular (8), colon (9) and pancreatic cancers (10). the mechanisms underlying these effects include the induction of apoptosis (3,7) and autophagy (9) and the suppression of aurora a kinase (8,10) in cancer cells.…”
mentioning
confidence: 99%
“…From ancient times, various parts of P. mume have been used as a health food and a medicinal agent for the treatment of fever, cough, and intestinal disorders. In addition, recent studies have reported that P. mume possesses various pharmacological activities, including inhibition of influenza A virus and motility of Helicobacter pylori, potential sources of free radical scavengers, improvement of blood fluidity, anti-inflammation, and anti-cancer action (21)(22)(23)(24)(25)(26)(27)(28). However, the cellular and molecular mechanisms responsible for the apoptotic effects of P. mume have not yet been determined in human cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have suggested that P. mume exerts a wide array of pharmacological and biological activities, such as potential sources of free radical scavengers, inhibition of influenza A virus, inhibition of the motility of Helicobacter pylori, improvement of blood fluidity, and inhibition of pro-inflammatory mediators (20)(21)(22)(23)(24)(25). In addition, P. mume has been known to exert anticancer activities in several types of human cancer cells (26)(27)(28). However, cellular and molecular mechanisms underlying the anti-cancer effects of P. mume are not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%